Comparison of different methods of cleaning and preparing occlusal fissure surface before placement of pit and fissure sealants: An in vivo study - Rahul J Hegde; Rochelle C Coutinho (Wolters Kluwer Medknow Publications, 2016)
Aim: To evaluate an individual method of cleaning and preparing occlusal fissure surface before placement of pit and fissure sealant and to determine a method for better retention of the sealant. Materials and Methods: The present study consisted of 100 young permanent molar teeth divided into four equal groups: Group 1-Brushing only, Group 2-Application of pumice slurry, Group 3-Surface conditioning, and Group 4-Control (without any preparation). Subsequent to fissure preparation, the fissures were etched using 37% phosphoric acid except for Group 3, which was etched using 10% maleic acid for 30 s. The samples were then rinsed for 10 s using air water spray of the three-way syringe and dried using oil-free compressed air with a hand pump air pressure syringe. After ensuring a frosted appearance of the enamel at the fissure entrance, pit and fissure sealants were applied on the surface according to manufacturer's instructions. All the cases were clinically evaluated for retention after 3 months, 6 months, and 12 months of application and the retention rate was assessed based on the criteria proposed by Simonsen. Results: The pumice slurry group and surface conditioning group showed results with 100%, 96%, and 92% complete retention seen at 3 months, 6 months, and 12 months, respectively. Conclusion: The pumice slurry group and surface conditioning group showed a significantly higher retention when compared to the brushing group, whereas the control group (without any preparation) showed the least retention when compared to all the other groups.